Static electrification in large power transformers - Zhang, Jian (2009)
Static electrification due to dielectric liquid flow has been found to be the cause of many field failures in the large forced-oil-cooled power transformers and in compact HVDC substations. The accumulation of static charge in the oil and isolated solid insulating surfaces causes the electric potential to rise in the same fashion as a Van de Graff generator. The potential builds up until either the rate of charge accumulation equals to the rate of charge leakage, or spark discharges occur. Though the problems of flow electrification were well recognized in petroleum industry, the charging mechanism and effect on transformer insulation and operation are still under active investigation.